Enforcement and Return of Evidence by the Public Prosecutor Following a Judge’s Decision to Grant Pardon - Natasya Audrey Christin Br. Marpaung; R.B. Sularto (Eduvest - Journal of Universal Studies, 2026)
This study addresses the legal uncertainty surrounding the execution and return of evidence following a judicial pardon (Rechterlijk Pardon) under Indonesia’s renewed criminal law framework. Although judicial pardon represents a shift toward restorative justice, the absence of specific prosecutorial procedures for implementing such decisions creates a normative gap, particularly when evidence must be returned to different entitled parties. This study aimed to analyze the normative position and authority of the Public Prosecutor in executing judicial pardon decisions and to formulate an appropriate mechanism for returning evidence. The research employed a normative juridical method using statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials, along with an illustrative analysis of Koto Baru District Court Decision Number 2/Pid.C/2026/PN Kbr. Data were analyzed qualitatively through grammatical, systematic, and teleological legal interpretation. The findings showed that prosecutors possessed legal authority to execute final judicial pardon decisions; however, specific administrative instruments remained insufficient, resulting in practical uncertainty. This study proposed a four-stage mechanism consisting of verification and classification, dual-track documentation, coordinated release, and monitoring and reporting. It concluded that technical prosecutorial regulations are necessary to ensure consistency, accountability, legal certainty, and the effective implementation of restorative justice in executing judicial pardon decisions.